Analysis of Ahok-Djarot News Framing After the 2017 Jakarta Regional Head Elections at Kompas and Tempo - Selsiana Paulina Gerong (COMMENTATE: Journal of Communication Management, 2022)
Kompas and Tempo were one of the national newspapers which highlighted the process of the Governor’s Election of DKI Jakarta on 2017. Those both newspapers were doing the framing for the news about the Governor’s Election of DKI Jakarta on 2017 to the readers. This research would focused on the framing analysis for every news about Ahok-Djarot on Kompas and Tempo after the election period, which would be specific for the certain period April 20-May 20 2017. The aim of the research is to conclude about what kind of framing that Kompas and Tempo did for Ahok-Djarot‘s news after the election at that period, to find out about the social construction which Kompas and Tempo designed and made. This research will use the qualitative research method; specifically use the framing analysis model by Zhongdang Pan and Gerald M. Kosicki. The result of this research would show the framing that Kompas and Tempo did is done by choosing the interviewees, choosing the quotes of the interviewees and choosing of the angle of photos which will support the news framing process. The social construction that Kompas made directing the opinions that Ahok is guilty and intentionally defaming religion by his words, it could be seen by the quotes that Kompas chose. In another side, the social construction that Tempo made tried to be neutral and directing the readers there were also another factors that make Ahok verdicted guilty as a defamer of religion and got two years in jail.